“Metal-bone” scaffold for accelerated peri-implant endosseous healing - Lu, Yue; Wang, Xianggang; Chen, Hao; Li, Xin; Liu, He; Wang, Jincheng; Qian, Zhihui (Frontiers in Bioengineering and Biotechnology, 2024)
Restoring bone defects caused by conditions such as tumors, trauma, or inflammation is a significant clinical challenge. Currently, there is a need for the development of bone tissue engineering scaffolds that meet clinical standards to promote bone regeneration in these defects. In this study, we combined the porous Ti6Al4V scaffold in bone tissue engineering with advanced bone grafting techniques to create a novel "metal-bone" scaffold for enhanced bone regeneration. Utilizing 3D printing technology, we fabricated a porous Ti6Al4V scaffold with an average pore size of 789 ± 22.69 μm. The characterization and biocompatibility of the scaffold were validated through in vitro experiments. Subsequently, the scaffold was implanted into the distal femurs of experimental animals, removed after three months, and transformed into a "metal-bone" scaffold. When this "metal-bone" scaffold was re-implanted into bone defects in the animals, the results demonstrated that, in comparison to a plain porous Ti6Al4V scaffold, the scaffold containing bone tissue achieved accelerated early-stage bone regeneration. The experimental group exhibited more bone tissue generation in the early stages at the defect site, resulting in superior bone integration. In conclusion, the "metal-bone" scaffold, containing bone tissue, proves to be an effective bone-promoting scaffold with promising clinical applications.